Pengaruh Karakteristik Pribadi dan Komitmen Organisasi Terhadap Loyalitas Pegawai Negeri Sipil Dinas Perindustrian Perdagangan dan Pengelolaan Pasar Kabupaten Indragiri Hulu - Indah Hardianty; Nuryanti '; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to find out influence of personal characteristic and organizational commitment on civil servants loyalty in Dinas Perindustrian Perdagangan dan Pengelolaan Pasar Kabupaten Indragiri Hulu. Population in this research is all of civil servants in Dinas Perindustrian Perdagangan dan Pengelolaan Pasar Kabupaten Indragiri Hulu. Sample which is taken is done with making all of population to be respondents and there are 61 respondents. Data source from primary data and secondary data. Technique of collecting data in this research are through an observation, interview, and questionnaire. Analysis method which is used quantitative descriptive method that use multiple linear regression constructively SPSS program version 17. Result shows that organizational commitment variable has significant influence to civil servants loyalty and more dominant than personal characteristic variable. Personal Characteristic has significant influence to civil servants loyalty in Dinas Perindustrian Perdagangan dan Pengelolaan Pasar Kabupaten Indragiri Hulu. Simultaneous test shows that personal characteristic variable and organizational commitment variable has significant influence depends on civil servants loyalty in Dinas Perindustrian Perdagangan dan Pengelolaan Pasar Kabupaten Indragiri Hulu which are described on R2 0,557. Means that Personal Characteristic and Organizational Commitment variables has influenced loyalty by 55,7% while the rest 44,3% is influenced by other variables which are not examined in this study.Keywords : Personal Characteristic, Organizational Commitment, Loyalty